Capsaicin‐mediated repair of circadian disruption‐induced Intestinal barrier damage via the gut microbiota - Yupei Deng; Bolin Lin; Chi‐Tang Ho; Jie Xiao; Yong Cao; Jun‐qing Huang; Muwen Lu (Food Frontiers)
Abstract Circadian clock serves as a regulator of gastrointestinal health, and the disruption of circadian rhythm may trigger the dysregulation of the intestinal barrier functions. This study investigated the effectiveness of capsaicin (CAP) in mitigating intestinal barrier dysfunction induced by circadian disruption in male SPF C57BL/6J mice. Our findings indicated that CAP supplementation attenuated abnormal weight gain, alterations in serum lipid levels, and misalignment in hepatic and colonic circadian clock gene expressions in mice caused by constant darkness (CD) treatment. The restoration of the intestinal barrier integrity was also observed through the increase in mucosal thickness and goblet cell numbers. Both the diversity and the circadian rhythm of gut microbiota were improved in CAP‐treated group. Correlation analysis indicated that CAP could modulate the gut microbiota by affecting intestinal barrier function and systemic metabolism in CD‐treated mice. These results highlight the potential of CAP as a functional food component in maintaining the intestinal barrier homeostasis through regulating gut microbiota.